The spectacle of flight : aviation and the Western imagination, 1920 - 1950 - Wohl, Robert, 1936- 1936- (Yale Univ. Press, 2005)
In the decades following the First World War, when aviation was still a revelation, flight was perceived as a spectacle to delight the eyes and stimulate the imagination. Historian Wohl takes us back to this time, recapturing the achievements of pioneering aviators and exploring flight as a source of cultural inspiration in the United States and Europe. He begins with an account of the impact of Lindbergh's dramatic New York-Paris flight, then explains how Mussolini identified his Fascist regime with the modernist cachet of aviation. Wohl shows how the Hollywood motion picture industry--drawing on the talents of such director-flyers as William Wellman and Howard Hawks and the eccentric millionaire Howard Hughes--created the aviation film; how writers such as Antoine de Saint-Exupéry helped foster France's self-image as the "winged nation"; and how the spectacle of flight reached its tragic apotheosis during the bombing campaigns of the Spanish Civil War and World War II.--From publisher description.